(untitled) (Journal of the Bangladesh Agricultural University, 2019)
Poultry manure is a hazard to the environment and health due to the release of toxic substances as well as pathogenic microorganisms. The present study was undertaken to assess the current scenario of poultry waste management considering its social as well as environmental and health hazards. A questionnaire based survey was conducted in 36 commercial poultry farms (which included 15 broiler, 14 layer, 3 cockerel and 4 mixed farms) in Mymensingh district from February to June 2016. Most of the broiler and layer farms had between 500 to 2000 birds, while most of the cockerel farms had between 3000 to 4000 birds. The study showed that 69 percent of the poultry farmers were unaware of the health and environmental problems of the poultry waste. Majority of the small scale farmers disposed their droppings to fish ponds (31 percent) and agricultural farms (16 percent) directly, while only 6 percent farmers used those droppings in biogas plant. However, 53 percent farmers had knowledge about hygienic handling of poultry dropping, although only 19 percent of them used protective gloves during dropping handling. The profitability analysis revealed that average variable cost and fixed cost per farm per year were TK. 2,17,355 and TK. 3,93,106, respectively. The benefit cost ratio per farm per year poultry farming was 1.55. Considering the findings, it is suggested that proper poultry waste management could be highly beneficial for the farmers. On the other hand, improper dispose of poultry litter could be a cause for social, environmental and public health hazard. J. Bangladesh Agril. Univ. 17(1): 50–57, March 2019